A Simple, Serendipitous Synthesis of Heterohexahelicenes. Issue 38 (2nd October 2019) - Dougherty, Kelly J.; Qin, Qian; Cruz, Ricardo; Cho, Yeyoung; Donahue, James P.; Mague, Joel T.; Wilson, Laura J.; Kraml, Christina M.; Pascal, Robert A.
Abstract : Oxidation of benzo[1, 2‐ b :3, 4‐ b ′:5, 6‐ b ′′]trithiophene (1 ) with MCPBA at room temperature gives the corresponding monosulfone 3 . This material readily undergoes a Diels–Alder dimerization with extrusion of SO2 to form the dihydroheterohelicene 5 . This, in turn, is easily converted into the heterohelicene 6 in a one‐pot NBS bromination and elimination. In a similar manner, oxidation of phenanthro[9, 10‐ b ]thiophene (12 ) gives the dihydroheterohelicene 13, and bromination/elimination forms the corresponding heterohelicene 8 . The X‐ray structures of compounds 5, 6, and 13 are reported, as well as computational studies that illuminate the unusual regiochemical outcome of the dimerization reactions. Abstract : MCPBA oxidation of triphenylene‐shaped, benzannulated thiophenes results in monosulfones that undergo Diels–Alder dimerization and extrusion of SO2 to give dihydroheterohelicenes. These, in turn, are easily converted into the corresponding heterohelicenes.